‘We’re getting there’: Registrar and examiner perspectives on structured oral examinations in emergency medicine - Sa’ad Lahri; Rhoda Meyer (Journal of the Colleges of Medicine of South Africa)
Background: Structured oral examinations (SOEs) are essential for assessing clinical competence in postgraduate emergency medicine qualifications. The rapid shift to web-based SOEs during the coronavirus disease 2019 pandemic and their continued use warrants an exploration of their effectiveness to identify areas for improvement in high-stakes assessments.